Accessing lanthanide-based, in situ illuminated optical turn-on probes by modulation of the antenna triplet state energy. Issue 27 (21st June 2021) - Cosby, Alexia G.; Woods, Joshua J.; Nawrocki, Patrick; Sørensen, Thomas J.; Wilson, Justin J.; Boros, Eszter
Abstract : The rational, analyte-mediated modulation of the relative energy of the lanthanide-sensitizing triplet state produces Tb-based luminescence, observable by a conventional optical imager in presence of the Cherenkov radiation emitting radioisotope 18 F. Abstract : Luminescent lanthanides possess ideal properties for biological imaging, including long luminescent lifetimes and emission within the optical window. Here, we report a novel approach to responsive luminescent Tb(iii ) probes that involves direct modulation of the antenna excited triplet state energy. If the triplet energy lies too close to the 5 D4 Tb(iii ) excited state (20 500 cm −1 ), energy transfer to 5 D4 competes with back energy transfer processes and limits lanthanide-based emission. To validate this approach, a series of pyridyl-functionalized, macrocyclic lanthanide complexes were designed, and the corresponding lowest energy triplet states were calculated using density functional theory (DFT). Subsequently, three novel constructs L3 (nitro-pyridyl), L4 (amino-pyridyl) and L5 (fluoro-pyridyl) were synthesized. Photophysical characterization of the corresponding Gd(iii ) complexes revealed antenna triplet energies between 25 800 and 30 400 cm −1 and a 500-fold increase in quantum yield upon conversion of Tb(L3 ) to Tb(L4 ) using the biologically relevant analyte H2 S. The corresponding turn-on reaction can be monitored using conventional, small-animal optical imaging equipment in presence of a Cherenkov radiation emitting isotope as an in situ excitation source, demonstrating that antenna triplet state energy modulation represents a viable approach to biocompatible, Tb-based optical turn-on probes.